The Influence of Promotion and Discount with Hedonic Shopping Motivation as Intervening Variable on Impulse Buying on E-Commerce Shopee - Ayu, Ira Porbonovitaning; Thamrin, Mohammad; Martini, Ni Nyoman Putu; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Technology plays an important role and dominates almost all business sectors, including in encouraging the emergence of new habits, namely online shopping. One of the platforms used to start an online business is the Shopee marketplace. Currently, many business people are starting to sell through e-commerce. This study aims to analyze the effect of promotions and discounts with hedonic shopping motivation as an intervening variable on impulse buying in Shopee e-commerce (Study on Jember Regency Government Employees Active Shopee Users). This study is quantitative and uses SmartPLS. The study population was female employees within the Jember Regency Government with a sample of 100 respondents. Instrument testing was carried out through validity tests, reliability tests, assumption tests, and hypothesis tests. The results of the study indicate that promotions and discounts carried out by Shopee have an impact on the hedonic shopping motivation of female employees. Promotions carried out by Shopee have a positive and significant effect on impulse buying. Discounts given by Shopee have no impact on impulse buying. The hedonic shopping motivation of these female employees has a positive and significant impact on impulse buying. While promotions and discounts have a positive and significant effect on impulse buying through hedonic shopping motivation.